The Inefficiency of inequality (UN ECLAC SantiagoCL, 2018)
Shows that social gaps and lags have a negative impact on productivity, fiscal policy, environmental sustainability and the spread of the knowledge society. Emphasises that equality is an inescapable ethical obligation and that equal rights, which are an intrinsic value of citizenship and modern humanism, must be consolidated in institutions, structures and policies toah help to close gaps.
Keywords: SOCIAL INEQUALITY